(Re)Reading, Reflexivity, and Peak-Experiences in Cao Xueqin's Honglou Meng - Ferrara, Mark S. (Literature and theology, 2018)
Many of Cao Xueqin's narrative innovations are exceptional for allowing him to engage his readers in a complex hermeneutical game-one in which the entire narrative is transformed into a multifaceted riddle (a type of Buddhist koan) that requires proper decipherment-and which ultimately seeks to transfer, by way of a mind-to-mind transmission, a highly particular state of perception by repeatedly calling attention to the fictionality of the text. In deploying innovative forms of reflexive inversion (such as doubling, dreaming, and punning), Cao Xueqin encourages his audience to become aware of the presence of the author, the artifice of the novel, and the paradox of fiction as a vehicle for religious truth.